Aplikasi Facebook Sebagai Sarana Dalam Berkatekese - Viktoria Stela Reyaan; Intan Sakti Pius X (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2023)
World progress is felt in various aspects and is very dominant in the field of technology, the development of digitalization makes the world without borders because it reaches every group in all corners of the world. Various applications are offered to make friends through this virtual world and the one that is very popular at the moment is Facebook. Facebook accounts have become popular among people because apart from the interesting features, Facebook can easily access friends without having to meet physically. The development of technological advances is considered good because it helps facilitate the movement of the world in seeking information and obtaining knowledge that supports needs in work, education and entertainment. Because the influence of technology reaches all aspects and influences the way today's users think and act, the impact of this change cannot be separated from the Church's anxiety about the development of the faith of its people. This article will explain the integrity of journalists which has developed in line with advances in digitalization. The author focused his presentation on using a Facebook account for catechesis.